Early and long-term performance evaluation of low NaOH concentrated waste HBP-GGBS based alkali activated composites - Mine Kurtay-Yıldız (Engineering Science and Technology, an International Journal)
This study investigates the long-term (365 days) performance of alkali activated composites (AACs) produced using GGBS and waste hollow brick powder (HBP) and activated with a low concentration (6 M) NaOH solution. Furthermore, it evaluated mechanical strength, durability and microstructure properties together, focusing on long-term performance analysis, which is limited in the literature. Mechanical properties, including compressive, flexural, and split tensile strengths, were evaluated over 7, 28, 90, 180, and 365 days, while durability tests (sulfate resistance, carbonation, and capillary water absorption) were carried out at 1, 3, 6, and 12 months. Microstructural analyses using XRD, FTIR, DTA-TGA and SEM-EDS were performed at 28 and 365 days. The results revealed significant improvements in mechanical performance over time, with compressive, flexural, and split tensile strengths reaching 77.05 MPa, 7.78 MPa, and 2.63 MPa at 365 days, respectively. Regression analysis showed strong correlations between compressive and flexural strengths and moderate to strong correlations between tensile and flexural strengths. Durability evaluations revealed resistance to sulfate attack and carbonation, emphasizing the long-term stability of the material under aggressive environmental conditions. Furthermore, microstructural findings confirmed the formation of intact gel phases, emphasizing the importance of curing time and the complementary nature of these analytical methods. This study determined the importance of curing time in optimizing the mechanical and durability properties of waste HBP-GGBS based AACs. In addition, this study demonstrates the potential of waste HBP-GGBS based AACs as sustainable, durable, and high-performance construction materials.